Security Analysis of BigBlueButton and eduMEET - Heitmann, Nico; Siewert, Hendrik; Moog, Sven; Somorovsky, Juraj (Applied Cryptography and Network Security)
Video conferencing systems have become an indispensable part of our world. Using video conferencing systems implies the expectation that online meetings run as smoothly as in-person meetings. Thus, online meetings need to be just as secure and private as in-person meetings, which are secured against disruptive factors and unauthorized persons by physical access control mechanisms. To show the security dangers of conferencing systems and raise general awareness when using these technologies, we analyze the security of two widely used research and education open-source video conferencing systems: BigBlueButton and eduMEET. Because both systems are very different, we analyzed their architectures, considering the respective components with their main tasks, features, and user roles. In the following systematic security analyses, we found 50 vulnerabilities. These include broken access control, NoSQL injection, and denial of service (DoS). The vulnerabilities have root causes of different natures. While BigBlueButton has a lot of complexity due to many components, eduMEET, which is relatively young, focuses more on features than security. The sheer amount of results and the lack of prior work indicate a research gap that needs to be closed since video conferencing systems continue to play a significant role in research, education, and everyday life.

We Really Need to Talk About Session Tickets: A Large-Scale Analysis of Cryptographic Dangers with TLS Session Tickets - Hebrok, Sven Niclas; Nachtigall, Simon; Maehren, Marcel; Erinola, Nurullah; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (32nd USENIX Security Symposium)

Security Analysis of the 3MF Data Format - Rossel, Jost; Mladenov, Vladislav; Somorovsky, Juraj (Proceedings of the 26th International Symposium on Research in Attacks, Intrusions and Defenses)

Re-Envisioning Industrial Control Systems Security by Considering Human Factors as a Core Element of Defense-in-Depth - Pottebaum, Jens; Rossel, Jost; Somorovsky, Juraj; Acar, Yasemin; Fahr, René; Arias Cabarcos, Patricia; Bodden, Eric; Gräßler, Iris (2023 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW))
The security of Industrial Control Systems is relevant both for reliable production system operations and for high-quality throughput in terms of manufactured products. Security measures are designed, operated and maintained by different roles along product and production system lifecycles. Defense-in-Depth as a paradigm builds upon the assumption that breaches are unavoidable. The paper at hand provides an analysis of roles, corresponding Human Factors and their relevance for data theft and sabotage attacks. The resulting taxonomy is reflected by an example related to Additive Manufacturing. The results assist in both designing and redesigning Industrial Control System as part of an entire production system so that Defense-in-Depth with regard to Human Factors is built in by design.
Keywords: Defense-in-Depth; Human Factors; Production Engineering; Product Design; Systems Engineering

Poster: Circumventing the GFW with TLS Record Fragmentation - Niere, Niklas; Hebrok, Sven Niclas; Somorovsky, Juraj; Merget, Robert (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)
State actors around the world censor the HTTPS protocol to block access to certain websites. While many circumvention strategies utilize the TCP layer only little emphasis has been placed on the analysis of TLS-a complex protocol and integral building block of HTTPS. In contrast to the TCP layer, circumvention methods on the TLS layer do not require root privileges since TLS operates on the application layer. With this proposal, we want to motivate a deeper analysis of TLS in regard to censorship circumvention techniques. To prove the existence of such techniques, we present TLS record fragmentation as a novel circumvention technique and circumvent the Great Firewall of China (GFW) using this technique. We hope that our research fosters collaboration between censorship and TLS researchers.

"I don' know why I check this..." - Investigating Expert Users' Strategies to Detect Email Signature Spoofing Attacks - Mayer, Peter; Poddebniak, Damian; Fischer, Konstantin; Brinkmann, Marcus; Somorovsky, Juraj; Sasse, Angela; Schinzel, Sebastian; Volkamer, Melanie (Eighteenth Symposium on Usable Privacy and Security (SOUPS 2022))

TLS-Anvil: Adapting Combinatorial Testing for TLS Libraries - Maehren, Marcel; Nieting, Philipp; Hebrok, Sven Niclas; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (31st USENIX Security Symposium (USENIX Security 22))

On the Security of Parsing Security-Relevant HTTP Headers in Modern Browsers - Siewert, Hendrik; Kretschmer, Martin; Niemietz, Marcus; Somorovsky, Juraj (2022 IEEE Security and Privacy Workshops (SPW))
Web browsers are among the most important but also complex software solutions to access the web. It is therefore not surprising that web browsers are an attractive target for attackers. Especially in the last decade, security researchers and browser vendors have developed sandboxing mechanisms like security-relevant HTTP headers to tackle the problem of getting a more secure browser. Although the security community is aware of the importance of security-relevant HTTP headers, legacy applications and individual requests from different parties have led to possible insecure configurations of these headers. Even if specific security headers are configured correctly, conflicts in their functionalities may lead to unforeseen browser behaviors and vulnerabilities. Recently, the first work which analyzed duplicated headers and conflicts in headers was published by Calzavara et al. at USENIX Security [1]. The authors focused on inconsistent protections by using both, the HTTP header X-Frame-Options and the framing protection of the Content-Security-Policy. We extend their work by analyzing browser behaviors when parsing duplicated headers, conflicting directives, and values that do not conform to the defined ABNF metalanguage specification. We created an open-source testbed running over 19,800 test cases, at which nearly 300 test cases are executed in the set of 66 different browsers. Our work shows that browsers conform to the specification and behave securely. However, all tested browsers behave differently when it comes, for example, to parsing the Strict-Transport-Security header. Moreover, Chrome, Safari, and Firefox behave differently if the header contains a character, which is not allowed by the defined ABNF. This results in the protection mechanism being fully enforced, partially enforced, or not enforced and thus completely bypassable.

ALPACA: Application Layer Protocol Confusion - Analyzing and Mitigating Cracks in TLS Authentication - Brinkmann, Marcus; Dresen, Christian; Merget, Robert; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schwenk, Jörg; Schinzel, Sebastian (30th USENIX Security Symposium (USENIX Security 21))

Raccoon Attack: Finding and Exploiting Most-Significant-Bit-Oracles in TLS-DH(E) - Merget, Robert; Brinkmann, Marcus; Aviram, Nimrod; Somorovsky, Juraj; Mittmann, Johannes; Schwenk, Jörg (30th USENIX Security Symposium (USENIX Security 21))

Automated Detection of Side Channels in Cryptographic Protocols: DROWN the ROBOTs! - Drees, Jan Peter; Gupta, Pritha; Hüllermeier, Eyke; Jager, Tibor; Konze, Alexander; Priesterjahn, Claudia; Ramaswamy, Arunselvan; Somorovsky, Juraj (14th ACM Workshop on Artificial Intelligence and Security)

Analysis of DTLS Implementations Using Protocol State Fuzzing - Fiterau-Brostean, Paul; Jonsson, Bengt; Merget, Robert; de Ruiter, Joeri; Sagonas, Konstantinos; Somorovsky, Juraj (29th USENIX Security Symposium (USENIX Security 20))

Mitigation of Attacks on Email End-to-End Encryption - Schwenk, Jörg; Brinkmann, Marcus; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schinzel, Sebastian (Proceedings of the 2020 ACM SIGSAC Conference on Computer and Communications Security)
OpenPGP and S/MIME are two major standards for securing email communication introduced in the early 1990s. Three recent classes of attacks exploit weak cipher modes (EFAIL Malleability Gadgets, or EFAIL-MG), the flexibility of the MIME email structure (EFAIL Direct Exfiltration, or EFAIL-DE), and the Reply action of the email client (REPLY attacks). Although all three break message confidentiality by using standardized email features, only EFAIL-MG has been mitigated in IETF standards with the introduction of AEAD algorithms. So far, no uniform and reliable countermeasures have been adopted by email clients to prevent EFAIL-DE and REPLY attacks. Instead, email clients implement a variety of different ad-hoc countermeasures which are only partially effective, cause interoperability problems, and fragment the secure email ecosystem.We present the first generic countermeasure against both REPLY and EFAIL-DE attacks by checking the decryption context including SMTP headers and MIME structure during decryption. The decryption context is encoded into a string DC and used as Associated Data (AD) in the AEAD encryption. Thus the proposed solution seamlessly extends the EFAIL-MG countermeasures. The decryption context changes whenever an attacker alters the email source code in a critical way, for example, if the attacker changes the MIME structure or adds a new Reply-To header. The proposed solution does not cause any interoperability problems and legacy emails can still be decrypted. We evaluate our approach by implementing the decryption contexts in Thunderbird/Enigmail and by verifying their correct functionality after the email has been transported over all major email providers, including Gmail and iCloud Mail.
Keywords: decryption contexts; EFAIL; OpenPGP; S/MIME; AEAD

"Johnny, you are fired!" -- Spoofing OpenPGP and S/MIME Signatures in Emails - Müller, Jens; Brinkmann, Marcus; Poddebniak, Damian; Böck, Hanno; Schinzel, Sebastian; Somorovsky, Juraj; Schwenk, Jörg (28th USENIX Security Symposium (USENIX Security 19))

Scalable Scanning and Automatic Classification of TLS Padding Oracle Vulnerabilities - Merget, Robert; Somorovsky, Juraj; Aviram, Nimrod; Young, Craig; Fliegenschmidt, Janis; Schwenk, Jörg; Shavitt, Yuval (28th USENIX Security Symposium (USENIX Security 19))

Security Analysis of XAdES Validation in the CEF Digital Signature Services (DSS) - Engelbertz, Nils; Mladenov, Vladislav; Somorovsky, Juraj; Herring, David; Erinola, Nurullah; Schwenk, Jörg (Open Identity Summit 2019)

Prime and Prejudice: Primality Testing Under Adversarial Conditions - Albrecht, Martin R.; Massimo, Jake; Paterson, Kenneth G.; Somorovsky, Juraj (Proceedings of the 2018 ACM SIGSAC Conference on Computer and Communications Security)

Attacking Deterministic Signature Schemes Using Fault Attacks - Poddebniak, Damian; Somorovsky, Juraj; Schinzel, Sebastian; Lochter, Manfred; Rosler, Paul (2018 IEEE European Symposium on Security and Privacy (EuroS&P))

On The (In-)Security Of JavaScript Object Signing And Encryption - Detering, Dennis; Somorovsky, Juraj; Mainka, Christian; Mladenov, Vladislav; Schwenk, Jörg (Proceedings of the 1st Reversing and Offensive-oriented Trends Symposium on - ROOTS)

Efail: Breaking S/MIME and OpenPGP Email Encryption using Exfiltration Channels - Poddebniak, Damian; Dresen, Christian; Müller, Jens; Ising, Fabian; Schinzel, Sebastian; Friedberger, Simon; Somorovsky, Juraj; Schwenk, Jörg (27th USENIX Security Symposium (USENIX Security 18))